The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1073/pnas.0810388105
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of complex traits: Large phenotypic effects and pervasive epistasis

Abstract: The genetic architecture of complex traits underlying physiology and disease in most organisms remains elusive. We still know little about the number of genes that underlie these traits, the magnitude of their effects, or the extent to which they interact. Chromosome substitution strains (CSSs) enable statistically powerful studies based on testing engineered inbred strains that have single, unique, and nonoverlapping genetic differences, thereby providing measures of phenotypic effects that are attributable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
244
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(266 citation statements)
references
References 32 publications
22
244
0
Order By: Relevance
“…However, we propose that these additional loci, in combination, can contribute to the high mtDNA instability observed in the extreme F 1 segregant (Figure 2, arrowhead). Similar epistatic interactions that are hard to detect by conventional genetic crosses have been uncovered by using whole-chromosome substitutions in mammals (Shao et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, we propose that these additional loci, in combination, can contribute to the high mtDNA instability observed in the extreme F 1 segregant (Figure 2, arrowhead). Similar epistatic interactions that are hard to detect by conventional genetic crosses have been uncovered by using whole-chromosome substitutions in mammals (Shao et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There is no significant variation among the categories (F = 1.8, df = 5, P = 0.109). Mapping multiple traits in chromosome substitution strains in mice gives a similar picture of the genetic architecture of quantitative phenotypes (Shao et al 2008). CSS studies of 90 traits in a mouse panel and 54 traits in a rat panel identified multiple QTLs for each phenotype (Shao et al 2008).…”
Section: How Much Does Genetic Architecture Vary Between Phenotypes?mentioning
confidence: 95%
“…Mapping multiple traits in chromosome substitution strains in mice gives a similar picture of the genetic architecture of quantitative phenotypes (Shao et al 2008). CSS studies of 90 traits in a mouse panel and 54 traits in a rat panel identified multiple QTLs for each phenotype (Shao et al 2008). The average Cold Spring Harbor Laboratory Press on May 11, 2018 -Published by genome.cshlp.org Downloaded from phenotypic effects for a CSS were similar across all phenotypes in both mouse and rat panels.…”
Section: How Much Does Genetic Architecture Vary Between Phenotypes?mentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the dissection of complex traits in animal models using chromosome substitution strains has shown that the number of strong effects may be larger than previously assumed and that substantial epistatic interactions account for the subadditivity of these effects. 23 Nonetheless, the detection by association analysis of more than a few effects contributing to a phenotype will demand very large samples. To limit the sample size, several strategies have been proposed.…”
Section: Discussionmentioning
confidence: 99%